Community of soil-inhabiting myxomycetes shares similar assembly mechanisms with fungi, and is affected by bacterial community in subtropical forests of China. (December 2022) - Gao, Yang; Song, Haiyan; Zhou, Fan; Chen, Shuanglin; He, Gang; Yan, Junqing; Sun, Qibiao; Long, Haozhi; Zhai, Zhijun; Hu, Dianming; Hu, Haijing
Abstract: Myxomycetes (Myxogastrea) are found in soil as myxamoebae and are a major component of the soil protist flora. Yet, our understanding of the drivers of myxamoebae community assembly lags far behind that of other protist groups. In this study we simultaneously investigate the spatial patterns of myxamoebae and their prey (bacteria and fungi communities) across eight subtropical forests in China, and aim to identify the ecological processes that determine the community assembly of myxamoebae. We found that all three microbial communities exhibited significant distance–decay relationships, with a higher degree of community concordance between myxamoebae and fungi than between myxamoebae and bacteria. The community turnover of both myxamoebae and fungi was primarily influenced by deterministic processes, whereas bacterial assembly was dominant by stochastic processes. Variation partitioning analysis showed that bacterial community structure explained the largest portion of the community turnover of myxamoebae, followed by spatial factors. Co-occurrence network analyses further revealed that myxamoebae had more potential interactions with bacteria than fungi, but did not target specific bacterial or fungal taxa. Overall, the significant effects of biotic and spatial factors on myxamoebae community assembly are critical to deciphering the distribution and function of these ecologically important microorganisms in soil environments. Highlights: Myxamoebae community exhibited a significant distance-decay pattern across subtropical forests in China. Myxamoebae community showed community concordance with fungi and bacteria. Deterministic processes predominated the myxamoebae and fungal community assembly. Bacterial community explained the largest portion of the community turnover of myxamoebae.